Dribbling Techniques in Football Games for Students - Sudirman, Sudirman; Adil, Ahmad; Ridwan, Andi (Sains Global Institut, Indonesia, 2024)
This research aims to find out the basic techniques for dribbling the ball among students. This research is a type of quantitative descriptive research that aims to reveal the dribbling abilities of students at SMAN 8 Sinjai. The population in this study was 230 students of SMAN 8 Sinjai. The sample in this research was 30 students of SMAN 8 Sinjai. This sample was drawn using a random sampling technique or a random method. The data analysis techniques used were descriptive, data normality, and categorization using the SPSS Version 22.00 system at a significance level of 95%. Based on the results of the research and discussion, the following conclusion can be drawn: The results of the ball dribbling ability test in the football game at UPT SMA Negeri 8 Sinjai can be categorized as good with an average score of 81.67 (descriptive data results).